Interdisciplinarity in practice: Reflections from early-career researchers developing a risk-informed decision support environment for Tomorrow's cities. (1st February 2023) - Filippi, M.E.; Barcena, A.; Šakić Trogrlić, R.; Cremen, G.; Menteşe, E.Y.; Gentile, R.; Creed, M.J.; Jenkins, L.T.; Kalaycioglu, M.; Poudel, D.P.; Muthusamy, M.; Manandhar, V.; et al.
Abstract: The concept of disaster risk is cross-disciplinary by nature and reducing disaster risk has become of interest for various disciplines. Yet, moving from a collection of multiple disciplinary perspectives to integrated interdisciplinary disaster risk approaches remains a fundamental challenge. This paper reflects on the experience of a group of early-career researchers spanning physical scientists, engineers and social scientists from different organisations across the global North and global South who came together to lead the refinement, operationalisation and testing of a risk-informed decision support environment for Tomorrow's Cities (TCDSE). Drawing on the notions of subjects and boundary objects, members of the group reflect on their individual and collective journey of transgressing disciplinary boundaries across three case studies between June–December 2021: operationalisation process of the TCDSE; development of a virtual urban testbed as a demonstration case for the implementation of the TCDSE; and consolidation of frequently asked questions about the TCDSE for communication purposes. The paper argues that (1) the production of boundary objects in interdisciplinary research nurtures relations of reciprocal recognition and the emergence of interdisciplinary subjects; (2) the intrinsic characteristics of boundary objects define the norms of engagement between disciplinary subjects and constrain the expression of interdisciplinary contradictions; and (3) affects and operations of power explain the contingent settlement of interdisciplinary disagreements and the emergence of new knowledge. Activating the interdisciplinary capacities of early-career researchers across disciplines and geographies is a fundamental step towards transforming siloed research practices to reduce disaster risk.